1984
DOI: 10.1016/0014-5793(84)80619-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a factor inducing differentiation of mouse myeloid leukemic cells purified from conditioned medium of mouse Ehrlich ascites tumor cells

Abstract: A factor inducing differentiation of mouse myeloid leukemic cells (M1) into macrophages was purified to apparent homogeneity from 168 1 of CM of Ehrlich ascites tumor cells. The purified factor was halt‐maximally active at 2 × 10−11 M. The factor was analyzed by radioiodination, SDS‐polyacrylamide gel electrophoresis and autoradiography. Its M r was 40000–50000. On reduction, the factor lost activity, but showed no subunit structure. Treatment of the factor with endo‐β‐N‐acetylglucosaminidase F, but not endo‐β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
81
0
2

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 18 publications
1
81
0
2
Order By: Relevance
“…LIF is a 40-45 kDa monomeric glycoprotein belonging to the IL6 family of cytokines. It is a pleiotropic molecule known to induce differentiation of mouse myeloid leukaemic cells [17], regeneration of muscle [18] and nerve [19], and mesenchymal-to-epithelial transdifferentiation in the developing kidney [20], whereas it inhibits differentiation and promotes proliferation of embryonic stem cells [21]. The action of LIF is mediated by a functional LIF receptor composed of two signal-transducing proteins, LIF receptor-β (LIFR) and gp130.…”
Section: Introductionmentioning
confidence: 99%
“…LIF is a 40-45 kDa monomeric glycoprotein belonging to the IL6 family of cytokines. It is a pleiotropic molecule known to induce differentiation of mouse myeloid leukaemic cells [17], regeneration of muscle [18] and nerve [19], and mesenchymal-to-epithelial transdifferentiation in the developing kidney [20], whereas it inhibits differentiation and promotes proliferation of embryonic stem cells [21]. The action of LIF is mediated by a functional LIF receptor composed of two signal-transducing proteins, LIF receptor-β (LIFR) and gp130.…”
Section: Introductionmentioning
confidence: 99%
“…First described because of its ability to induce differentiation of murine M1 leukemia cells (3,4), D factor has been independently identified under several synonyms: leukemia inhibitory factor (LIF), differentiation-inhibiting factor (D factor), osteoclast-activating factor (OAF), human interleukin for DA-1 cells (HILDA), cholinergic neuronal differentiation factor (CNDF), hepatocyte-stimulating factor (HSF-II and III), and melanocyte-derived lipoprotein lipase inhibitor (MLPLI), and is now recognized to have pleiotropic actions in regulating metabolism, growth, and differentiation. Although diverse effects of D factor have been identified in vitro (5)(6)(7)(8)(9)(10)(11) and in vivo (12)(13)(14)(15)(16), little is known about its role during acute and chronic inflammation.…”
mentioning
confidence: 99%
“…Although diverse effects of D factor have been identified in vitro (5)(6)(7)(8)(9)(10)(11) and in vivo (12)(13)(14)(15)(16), little is known about its role during acute and chronic inflammation. It can be produced by a variety of cells, including fibroblasts (3,17), monocytes, macrophages (18), and T lymphocytes (19), and its synthesis can be induced by TNF, IL-1, and endotoxin (LPS) (17,20,21). In addition, elevated levels of D factor have been identified in the body fluids of patients with a variety of acute and chronic inflammatory conditions, such as septic shock, rheumatoid arthritis, renal aUograft rejection, and cancer (20,22,23).…”
mentioning
confidence: 99%
“…Extensive studies have documented the presence in various conditioned media of differentiation-inducing factors (DF, DIF or MGI-2) that do not appear to be proliferative agents but are able to induce similar suppressive effects to G-CSF on a variety of murine and human leukemic cell lines, the most extensively studied being the murine M1 model [31][32][33]. In vivo evidence indicates that production of the murine factor can be T -cell-dependent [34], unlike the situation with G-CSF, and biochemical purification studies have indicated that DF is separable and distinct from G-CSF [33,35]. Injection of crude material containing MGI-2 inhibited the growth of transplanted myeloid leukemic cells in SL and SJL/J mice [36], and it will be of interest to determine the structure and actions of this factor in vivo when cDNA clones and recombinant material can be obtained.…”
Section: E Other Biological Agents Suppressing Myeloid Leukemiamentioning
confidence: 99%